William Orton Tewson papers - Tewson, William Orton, 1877-1947.
List of contributors and responses from authors, poets, and journalists to Tewson's query, "Do you care what the critics say about you?", posed in the Literary Review of the New York Evening Post (1926 September 4), a weekly magazine that he edited. Includes a letter (1923 October 13) from Tewson to Mrs. George Donehower relating to Joseph Conrad. Correspondents include Sherwood Anderson, George Agnew Chamberlain, Hamlin Garland. Ben Hecht, Joseph Hergesheimer, Rupert Hughes, Fannie Hurst, Robinson Jeffers, Ring Lardner, Richard Le Gallienne, Sinclair Lewis, Edwin Markham, Edgar Lee Masters, H.L. Mencken, George Jean Nathan, Robert Nathan, Meredith Nicholson, Eugene O'Neill, Edwin Arlington Robinson, Upton Sinclair, Booth Tarkington, Louis Untermeyer, and Owen Wister.
Editor and literary critic.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Letter from Tewson to Mrs. George Donehower forms part of the Alfred Bendiner Memorial Collection (Library of Congress).
Keywords: Anderson, Sherwood, -- 1876-1941 -- Correspondence; Chamberlain, George Agnew, -- 1879-1966 -- Correspondence; Conrad, Joseph, -- 1857-1924.; Donehower, George. -- Mrs. -- Correspondence; Garland, Hamlin, -- 1860-1940 -- Correspondence; Hecht, Ben, -- 1894-1964 -- Correspondence; Hergesheimer, Joseph, -- 1880-1954 -- Correspondence; Hughes, Rupert, -- 1872-1956 -- Correspondence; Hurst, Fannie, -- 1889-1968 -- Correspondence; Jeffers, Robinson, -- 1887-1962 -- Correspondence; Lardner, Ring, -- 1885-1933 -- Correspondence; Le Gallienne, Richard, -- 1866-1947 -- Correspondence; Lewis, Sinclair, -- 1885-1951 -- Correspondence; Markham, Edwin, -- 1852-1940 -- Correspondence; Masters, Edgar Lee, -- 1868-1950 -- Correspondence; Mencken, H. L. -- 1880-1956 -- Correspondence; Nathan, George Jean, -- 1882-1958 -- Correspondence; Nathan, Robert, -- 1894-1985 -- Correspondence; Nicholson, Meredith, -- 1866-1947 -- Correspondence; O'Neill, Eugene, -- 1888-1953 -- Correspondence; Robinson, Edwin Arlington, -- 1869-1935 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Tarkington, Booth, -- 1869-1946 -- Correspondence; Untermeyer, Louis, -- 1885-1977 -- Correspondence; Wister, Owen, -- 1860-1938 -- Correspondence; Literary review (New York, N.Y.); New York evening post; American newspapers; Criticism; Critics; Editors